2023
DOI: 10.3390/microorganisms11081922
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genetic Characterization of CTX-M-Producing Escherichia coli Isolated from Humans and Pigs with Diarrhea in Korea Using Next-Generation Sequencing

Abstract: Pathogenic E. coli causes intra- and extraintestinal diseases in humans and pigs and third-generation cephalosporins are the primary option for the treatment of these diseases. The objective of this study was to investigate the characteristics and correlation between CTX-M-producing E. coli from humans and pigs regarding CTX-M-producing E. coli using next-generation sequencing and bioinformatic tools. Among the 24 CTX-M–producing E. coli, three types of CTX-M genes (CTX-M-12, CTX-M-14, and CTX-M-15) were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Group 1 CTX-M variants are the most widespread globally compared to other variants and in Africa and Asia, reports indicated that CTX-M group 1 are more common [ 10 , 15 ]. Of the CTX-M Group 1, CTX-M-15 is currently the dominant variant and a cause of concern in clinical practice [ 16 ]. The literature suggests that the CTX-M-15 gene variants are widely distributed in countries in Europe, North and South America as well as Asia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 1 CTX-M variants are the most widespread globally compared to other variants and in Africa and Asia, reports indicated that CTX-M group 1 are more common [ 10 , 15 ]. Of the CTX-M Group 1, CTX-M-15 is currently the dominant variant and a cause of concern in clinical practice [ 16 ]. The literature suggests that the CTX-M-15 gene variants are widely distributed in countries in Europe, North and South America as well as Asia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding specific E. coli pathotypes associated with CTX-M genes is scarce [ 19 ]. While CTX-M are the predominant ESBL genes encountered, two other genes, namely TEM, and SHV, which encode enzymes that confer beta-lactam resistance are also encountered in the Enterobacteriaceae group such as E. coli [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%